2017
DOI: 10.7554/elife.24767
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin signaling regulates heme biosynthesis

Abstract: Heme is required for survival of all cells, and in most eukaryotes, is produced through a series of eight enzymatic reactions. Although heme production is critical for many cellular processes, how it is coupled to cellular differentiation is unknown. Here, using zebrafish, murine, and human models, we show that erythropoietin (EPO) signaling, together with the GATA1 transcriptional target, AKAP10, regulates heme biosynthesis during erythropoiesis at the outer mitochondrial membrane. This integrated pathway cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 97 publications
(80 reference statements)
1
41
0
Order By: Relevance
“…Studies in stem cell-derived cardiomyocytes indicate that AKAP10 (D-AKAP2) is essential in controlling the heart rate and rhythm [ 25 ]. Recently, it was shown that AKAP10 is crucial in erythropoietin signaling and heme biosynthesis at the outer mitochondrial membrane [ 26 ]. Cardiac phosphoinositide 3-kinase gamma (PI3Kγ) is an AKAP that binds phosphodiesterase3B (PDE3B) and phosphatidylinositol (3,4,5)-trisphosphate (PtdIns(3,4,5)P3) along with PKA regulating cAMP and PtdIns(3,4,5)P3 signaling.…”
Section: Role Of Akaps In Cardiovascular Physiologymentioning
confidence: 99%
“…Studies in stem cell-derived cardiomyocytes indicate that AKAP10 (D-AKAP2) is essential in controlling the heart rate and rhythm [ 25 ]. Recently, it was shown that AKAP10 is crucial in erythropoietin signaling and heme biosynthesis at the outer mitochondrial membrane [ 26 ]. Cardiac phosphoinositide 3-kinase gamma (PI3Kγ) is an AKAP that binds phosphodiesterase3B (PDE3B) and phosphatidylinositol (3,4,5)-trisphosphate (PtdIns(3,4,5)P3) along with PKA regulating cAMP and PtdIns(3,4,5)P3 signaling.…”
Section: Role Of Akaps In Cardiovascular Physiologymentioning
confidence: 99%
“…6E), suggesting that its effects on FECH activity may be mediated by the requirement for FAM210B for efficient iron delivery to FECH, and/or by playing a role in allosteric activation of the FECH enzyme. These data add to our understanding of the mechanisms by which Epo signaling regulates heme synthesis by post-translational regulation of FECH (49) and suggest mechanisms by which the activity of heme synthetic enzymes, in this case, FECH, may be rapidly modulated in response to metabolic requirements.…”
Section: Discussionmentioning
confidence: 73%
“…To determine whether FAM210B functions as a mitochondrial iron importer or whether it played a role in regulation of FECH, we carried out an in vitro heme synthesis assay to compare the amount of iron transported across the mitochondrial membrane to synthesize deuteroheme (49). 55 Fe and DP were added to isolated mitochondria from WT and Fam210b Ϫ/Ϫ MEL cells.…”
Section: Fam210b Regulates Mitochondrial Iron Import and Fech Activitmentioning
confidence: 99%
“…For instance, erythroid cells shift from the use of the Krebs' cycle and oxidative phosphorylation to exclusive dependence on glycolysis as they terminally differentiate mitochondria (Gasko and Danon, 1972c, 1972a, 1972b. During terminal differentiation, the main function of erythroid mitochondria shifts towards heme production for hemoglobin synthesis (Chen et al, 2013;Chung et al, 2017;Yien et al, 2014Yien et al, , 2018Zhang et al, 2003). It is therefore unsurprising, but revealing, that CLPXP regulates erythroid heme synthesis at multiple points in the pathway, but does not seem to be as essential for regulating oxidative phosphorylation proteins as it does in other cell types.…”
Section: Discussionmentioning
confidence: 99%